Addressing Data Gaps with Innovative Data Sources - Jana Flor V. Vizmanos; Jose Ramon G. Albert; Mika S. Mu\~noz; Arlan Brucal; Riza Teresita Halili; Angelo Jose Lumba; Gaile Anne Patan\~ne (Philippine Institute for Development Studies (PIDS), 2022)
With the advent of digital transformation, ICT innovations have also led to a "data revolution" wherein more data is being captured, produced, stored, accessed, analyzed, archived, and reanalyzed, and at an exponential pace. An examination of new data sources, including big data and crowd-sourced data, can complement traditional sources of statistics and can unlock insights that can ultimately lead to interventions for better outcomes by informing policies and actions toward attaining robust, sustainable, and inclusive development. This study will examine PIDS website download data and Twitter data to illustrate stories that can be obtained from new data sources and explore how access, analysis and use of new data sources can be promoted. Several quantitative tools are used on these new data sources, including (a) market basket analysis for website download data, (b) text mining (and sentiment analysis) for web scraped Twitter data, and (c) other big data analytics tools. Policy issues, including risk management for use of these new data sources, are also discussed.
Keywords: 330; data revolution; big data; new data sources; social media data; market-basket analysis; web scraping; text mining; sentiment analysis